Prevalence of the Complaint of Ejaculating Prematurely and the Four Premature Ejaculation Syndromes: Results from the Turkish Society of Andrology Sexual Health Survey - Serefoglu, Ege C.; Yaman, Onder; Cayan, Selahittin; Asci, Ramazan; Orhan, Irfan; Usta, Mustafa F.; Kadioglu, Ates (Elsevier Sci Ltd, 2011)
Introduction. In addition to the previously known lifelong and acquired premature ejaculation (PE) syndromes, the existence of two more PE syndromes has been suggested: natural variable PE and premature-like ejaculatory dysfunction. However, epidemiological studies investigating the prevalence of these four PE syndromes have yet to be conducted. Aim. To determine the prevalence of the complaint of ejaculating prematurely across the four PE syndromes. Methods. This study, conducted between June 2009 and December 2009, was designed as a non-interventional, observational cross-sectional field survey. Participating couples were randomly selected from 17 provinces of Turkey. All participants were asked to complete a questionnaire including data regarding demographics, socioeconomic status, social and cultural factors, medical and sexual history, current medications, and ejaculation time. Subjects with a complaint of ejaculating prematurely were classified as lifelong, acquired, and natural variable PE, or premature-like ejaculatory dysfunction. Main Outcome Measures. The main outcome measures were prevalence of complaint of ejaculating prematurely in the general population and across the four PE syndromes. Results. A total of 2,593 couples (mean age, 41.9 +/- 12.7 years for males and 38.2 +/- 12.1 years for females) were enrolled. Five-hundred twelve subjects (20.0%) complained of ejaculating prematurely. Fifty-eight (2.3%), 100 (3.9%), 215 (8.5%), and 131 (5.1%) subjects were classified as lifelong, acquired, and natural variable PE, and premature-like ejaculatory dysfunction, respectively. Conclusions. The prevalence of the complaint of ejaculating prematurely among Turkish men was 20.0%, with the highest PE syndrome being natural variable PE (8.5%) and premature-like ejaculatory dysfunction (5.1%). Serefoglu EC, Yaman O, Cayan S, Asci R, Orhan I, Usta MF, Ekmekcioglu O, Kendirci M, Semerci B, and Kadioglu A. Prevalence of the complaint of ejaculating prematurely and the four premature ejaculation syndromes: Results from the Turkish Society of Andrology Sexual Health Survey. J Sex Med 2011;8:540-548.
Keywords: Epidemiology; Intravaginal Ejaculatory Latency Time; Lifetime and Acquired Ejaculatory Disorders; Premature Ejaculation; Prevalence; Premature Ejaculation Syndromes; Sexual Dysfunction